2003
DOI: 10.1046/j.1365-2133.2003.05070.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct stimulatory effect of low-intensity 670 nm laser irradiation on human endothelial cell proliferation

Abstract: Low-intensity laser irradiation influences EC proliferation and might thereby contribute to the increase in angiogenesis and the acceleration of wound healing in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 21 publications
4
53
0
11
Order By: Relevance
“…Angiogenesis, the growth of new vasculature, is a critical biological response to ischemia that provides collateralization, or ''biological revascularization'' of vascular obstructions [45]. Evidence exists to support the concept that a graft lined with a significant number of endothelial cells (EC) would consequently lead better graft survival [46] LELI has been demonstrated to positively influence cellular proliferation for the process of angiogenesis on EC [2,47]. Previous study has shown that the direct stimulation by low-intensity 670 nm laser irradiation could induce the proliferation on EC [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Angiogenesis, the growth of new vasculature, is a critical biological response to ischemia that provides collateralization, or ''biological revascularization'' of vascular obstructions [45]. Evidence exists to support the concept that a graft lined with a significant number of endothelial cells (EC) would consequently lead better graft survival [46] LELI has been demonstrated to positively influence cellular proliferation for the process of angiogenesis on EC [2,47]. Previous study has shown that the direct stimulation by low-intensity 670 nm laser irradiation could induce the proliferation on EC [47].…”
Section: Discussionmentioning
confidence: 99%
“…However, to date only a few studies have addressed the direct effects of laser irradiation on endothelial cell proliferation and migration [2,42,43]. The purpose of this study, therefore, was to determine the mechanisms by which LELI may exert some of its angiogenic effects via PI3 kinase/eNOS signaling pathway and induce endothelial cell migration and neovascularization, an important and necessary part of wound healing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell proliferation is a very important physiological effect for the low-level laser irradiation used in clinical practice. Increased proliferation after LLLI has been shown in many cell types in vitro, including fibroblasts from different systems (Kreisler et al 2002), keratinocytes (Grossman et al 1998), human osteoblasts (Stein et al 2005), calvaria osteoblast-like cells, mesenchymal stem cells and cardiac stem cells (Tuby et al 2007), rat Schwann cells (Van Breugel et al 2003), aortic smooth muscle cells (Gavish et al 2006), endothelial cells from veins (Schindl et al 2003) and arteries (Kipshidze et al 2001), quiescent satellite cells (Ben-Dov et al 1999), human lung adenocarcinoma cells (Shefer et al 2002) and HeLa cells (Zhang et al 2008). Various mechanisms for the mitogenic effects of low power laser irradiation have been proposed, including ligand-free dimerization and activation of specific receptors that are in the "right energetic state" to accept the laser energy, leading to their autophosphorylation and downstream effects (Zhang et al 2008), activation of calcium channels resulting in increased intracellular calcium concentration and cell proliferation (Breitbart et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that LLLT is effective in reducing overall body circumference measurements of specifically treated regions, including the hips, waist, thighs, and upper arms, with recent studies demonstrating the long-term effectiveness of results [8].…”
mentioning
confidence: 99%